PENGARUH RISIKO BISNIS, UKURAN PERUSAHAAN DAN PERTUMBUHAN PENJUALAN TERHADAP STRUKTUR MODAL - Ria, Yuliana; Lestari, Putu Vivi (E-Jurnal Manajemen, 2015)
The capital structure is balancing the number of short-term debt that is permanent, long-term preferred stock and common stock. To find out what may affect the capital structure to consider several factors such as business risk, Company Size, and Sales Growth. The purpose of this study to determine the influence of Business Risk, Company Size, and Growth Sales to Capital Structure. The research was conducted on the Stock Exchange by using a sample of 12 companies acquired by purposive sampling method and the data were analyzed with multiple linear regression analysis technique. Based on the analysis, it was found that the risk of business and company size does not significantly influence the capital structure while sales growth and a significant positive effect on the capital structure in the automotive industry in Indonesia Stock Exchange 2010-2013.
Keywords: business risk, firm size, sales growth and capital structure